Governing traditional cultural expressions as artificial intelligence training data: Reconstructing communal consent and data transparency in Indonesia - Muhammad Abdul Azis; Riski Ananda Kusuma Putri; Alya Synthia Kurniawati; Muhammad Thufail Ariiq (Societa: Journal of Society and Change, 2026)
The use of traditional cultural expressions as training data for generative artificial intelligence systems raises legal questions that individual copyright doctrine cannot adequately resolve. This study examines the legal status of traditional cultural expressions, the legitimacy of their use as training data, the position of source communities, and developers' transparency obligations under Indonesian law. It employs doctrinal legal research using statutory, conceptual, and comparative approaches. The findings demonstrate that Indonesian law recognizes state stewardship, inventory obligations, commercial-use authorization, and benefit sharing but does not regulate the classification of model training, procedures for communal consent, source traceability, or legal remedies. This article proposes the Cultural Training Data Legality Test, integrating legal status, community provenance, lawful acquisition, layered consent, purpose limitation, cultural integrity, transparency, benefit sharing, and remedies. For high-risk commercial uses, state authorization and representative community consent should apply cumulatively, with transparency serving as a foundation for accountability. Abstrak Pemanfaatan ekspresi budaya tradisional sebagai data pelatihan bagi sistem kecerdasan artifisial generatif menimbulkan persoalan hukum yang belum dapat dijawab secara memadai oleh rezim hak cipta individual. Penelitian ini menganalisis status hukum ekspresi budaya tradisional, legalitas penggunaannya sebagai data pelatihan, kedudukan komunitas asal, serta kewajiban transparansi pengembang dalam hukum Indonesia. Penelitian ini menggunakan metode penelitian hukum doktrinal dengan pendekatan peraturan perundang-undangan, konseptual, dan perbandingan. Hasil penelitian menunjukkan bahwa hukum Indonesia telah mengakui penguasaan negara, kewajiban inventarisasi, izin pemanfaatan komersial, dan pembagian manfaat, tetapi belum mengatur klasifikasi pelatihan model, prosedur persetujuan komunal, keterlacakan sumber, maupun mekanisme pemulihan hukum. Penelitian ini menawarkan Uji Legalitas Data Pelatihan Budaya yang mengintegrasikan status hukum, asal komunitas, legalitas perolehan, persetujuan berlapis, pembatasan tujuan, integritas budaya, transparansi, pembagian manfaat, dan mekanisme pemulihan. Untuk penggunaan komersial yang berisiko budaya tinggi, persetujuan negara dan komunitas perwakilan harus berlaku secara kumulatif, dengan transparansi berfungsi sebagai landasan akuntabilitas.